O projeto estético de Mia Couto : mito, tradição e diálogo em A Confissão da Leoa - Martins, Ilson Ferreira (2017)
The present research aims to analyze elements that we consider fundamental in the aesthetic project of the Mozambican writer Mia Couto, circumscribing the categories of myth, tradition and dialogue, starting from the novel The Confession of the Lioness (2012), of the mentioned author. In this sense, we try to demonstrate that this author seeks ways of saying not only one but several worlds, sometimes attributing to the literary the function of filling gaps in the imaginary that the words "ordinary" can not say. The result of this is a narrative composition that combines values inherent to the ancestral memory and / or the cultural traditions of Mozambique, in a kind of dialogue of these values with contemporary instances. In The Confession of the Lioness, the discourses of the narrators are permeated by remembrances that allow the emergence of voices, both from other characters that compose the plot, and from mythical instances and / or values of tradition, evoked in order to promote reflections on facts, real or imagined, pervaded in the daily life of Mozambican society. In this context, the author can both revisit a remote past, ancestral past, as well as a more recent past, sometimes revealing disturbing realities, including the subjugated condition of women vis-a-vis man, which is a more salient situation in rural communities of Mozambique. In short, myth, tradition and dialogue appear in the novel as modulating creations of possible worlds, anchored in the creative power of literary language. KEYWORDS: Mia Couto; Aesthetic project; Myth; Tradition; Dialogue